Political ideology in the correspondence of Julio Ramón Ribeyro with his brother Juan Antonio (1953-1983) - Coaguila, Jorge (2019)
The political content is one of the fundamental aspects in the correspondence of Julio Ramón Ribeyro with his brother Juan Antonio, sent from 1953 to 1983. The writer Lima outlines in her the most general features of his political ideology, a question not addressed or studied until today. These letters allow us to know in anextensive way the reflections of Ribeyro about the social reality of Peru and the world in a very whooping and complex time: the second half of the twentieth century. They are almost non-existent reflections in the rest of his fictional, literary or intellectual work in general. Thus, this correspondence possesses a high historical,theoretical and literary value expressed in a political ideological thought.